Model Konsep, Desain, Implementasi dan Pengembangan Kurikulum Pendidikan Agama Islam - Nanda Inka Fitri; Reni Susilaati; Eti Hadiati (MISYKAT Jurnal Ilmu-ilmu Al-Quran Hadist Syari ah dan Tarbiyah, 2024)
Education is always dynamic and continues to develop according to developments and progress over time. As is the case when entering an era of progress both in science and technology which is called the era of globalization which requires humans to adapt to the needs of the times. This happens in all lines of life, namely in the social, economic, political, cultural fields and also occurs in the educational sector. The changes that occur in all aspects of education are aimed at achieving the goals of education, Islam also supports changes in a positive direction and for the better. All aspects of education have also changed in all aspects, including changes to the curriculum as the foundation and framework for implementing the educational process. Curriculum changes in Indonesia have occurred since 1945. As prospective educators, especially educational practitioners, it is very important to study the Concept Model for Design of Implementation and Development of the Islamic Religious Education Curriculum. By using descriptive analysis methods through literature studies or library research, the author tries to examine every aspect of the Islamic Religious Education Curriculum Implementation and Development Design Concept Model in order to produce insight and knowledge and as a view to develop a guideline and reference in carrying out the process education.